2006
DOI: 10.1111/j.1464-5491.2006.01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and risk factors of severe hypoglycaemia in insulin‐treated Type 2 diabetes: a cross‐sectional survey

Abstract: In this cohort of insulin-treated Type 2 diabetic patients, the incidence of severe hypoglycaemia is higher than reported in most studies, corresponding to about one-third of that in Type 1 diabetes. Impaired hypoglycaemia awareness is the most important risk factor for severe hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
77
3
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 24 publications
(49 reference statements)
16
77
3
6
Order By: Relevance
“…A number of studies describing the frequency of SH have been published [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . However, most of these studies have been performed with a selected cohort 7,8,[11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies describing the frequency of SH have been published [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . However, most of these studies have been performed with a selected cohort 7,8,[11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies have been performed with a selected cohort 7,8,[11][12][13][14][15][16][17][18][19][20][21][22] . The incidence of SH varied from 0.038 to 3.2 episodes of SH per patient per year in patients with DM type 1 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…19,20,[25][26][27][28][29][30][31] However, some other studies found that ZIP model was better than ZINB model because of less severity of over-dispersion in those study data. [32][33] In addition, some studies considered ZIP model as a good model for count outcome data, but these studies did not explore the ZINB model and couldn't compare the goodness of fit between ZIP model and ZINB model.…”
Section: Results Of Zinb Modelmentioning
confidence: 70%
“…Ча-стота гипогликемий неизбежно увеличивается при боль-шой длительности диабета [38], длительном применении инсулина, а также у пациентов, получающих базис-бо-люсную инсулинотерапию [39].…”
Section: безопасность и переносимостьunclassified